Dietary resistant potato starch improves growth performance and feather development in Pekin ducks fed a low phosphorus diet - H.M. Xu; K.Y. Zhang; S.P. Bai; X.M. Ding; J.P. Wang; H.W. Peng; Y. Xuan; Z.W. Su; T. Gang; Q.F. Zeng (Poultry Science, 2021)
This study investigated whether dietary resistant potato starch (RPS) inclusion could ameliorate the negative impact of a low nonphytate phosphorus (nPP) diet on growth performance, feather growth, feather follicles (FF) development, and carcass traits by improving nutrient utilization and cecal microbiome fermentation capacity in Pekin ducks. The experiment was performed with a 2 × 2 randomized block design with 2 levels of RPS (0 or 12%) and 2 levels of nPP (low or normal, low: 0.22% at 1–14 d and 0.18% at 15–35 d of age; normal: 0.40% at 1–14 d and 0.35% at 15–35 d of age) for a total of 4 treatments, each with 8 replicate pens per treatment of 12 birds per pen. As regards growth performance and carcass traits, RPS inclusion markedly increased (P < 0.05) BW of 14 and 35 d, BWG and FI of 1–14 d, 15–35 d, and 1–35 d as well as abdominal fat and breast meat percentage of 35 d in ducks fed low nPP diets; moreover, RSP inclusion significantly reduced (P < 0.05) mortality in ducks fed low nPP diets. As regards feather growth and follicles development of 35 d, RPS inclusion significantly increased (P < 0.05) the fourth primary feather length, absolute feather weight, and the density of primary FF in the back skin in ducks fed low nPP diets. In regard to nutrition utilization, RPS supplementation significantly increased (P < 0.05) the availability of DM, CP, and energy, as well as dietary AME at 35 d of age in ducks fed low nPP diets. However, RPS supplementation had no effect (P > 0.05) on the concentration of cecal short-chain fatty acids and the activities of cecal phytase and cellulase in ducks fed low nPP diets. These results indicate that RPS can improve nutrient availability to ameliorate the negative effects on performance and feather development caused by a low nPP diet in Pekin ducks.